2010
DOI: 10.1177/0007650310362254
|View full text |Cite
|
Sign up to set email alerts
|

Eco-Labeling Strategies and Price-Premium

Abstract: Although there is increasing use of eco-labeling, conditions under which eco-labels can command price premiums are not fully understood. In this article, we demonstrate that the certification of environmental practices by a third party should be analyzed as a strategy distinct from-although related to-the disclosure of the eco-certification through a label posted on the product. By assessing eco-labeling and eco-certification strategies separately, researchers can identify benefits associated with the certific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
207
4
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 234 publications
(217 citation statements)
references
References 66 publications
5
207
4
1
Order By: Relevance
“…Information strategies are based on the principle that more and better information about the environmental impact of activities will encourage consumers to conserve. While theory suggests that information programs may be effective, the empirical evidence seems to indicate important differences in effectiveness according to type of information provided and the context in which the information is communicated (Delmas and Grant, 2010;.…”
Section: Introductionmentioning
confidence: 99%
“…Information strategies are based on the principle that more and better information about the environmental impact of activities will encourage consumers to conserve. While theory suggests that information programs may be effective, the empirical evidence seems to indicate important differences in effectiveness according to type of information provided and the context in which the information is communicated (Delmas and Grant, 2010;.…”
Section: Introductionmentioning
confidence: 99%
“…Formal certification also affects prices significantly, positively for biodynamic and negatively for organic wines in the American market (see also Delmas and Grant (2011)). Given that the clearest signal of membership in these categories comes from formal certification, this pair of results also supports our interpretation of the situation.…”
Section: Resultsmentioning
confidence: 99%
“…In fact, it tends to be regarded with favor in the wine world. Results from a consumer survey indicated that the majority of American respondents who had tasted organic wines had a positive opinion of their quality (Delmas and Grant, 2011). The French government and the European Commission also explicitly favor the use of organic practices and define them as "good for nature and good for consumer" (European Commission, 2010).…”
Section: Resultsmentioning
confidence: 99%
“…For some authors it has little or no influence (Schamel & Anderson, 2003;Schamel, 2006;Luppe et al, 2009), and for others it is a determining factor (Angulo et al, 2000;Lecocq & Visser, 2006;Schroeter et al, 2011) Finally, the inclusion of the winery size variable enables assessment of the impact of the scale factor on wine prices, as well as quantification of the exclusiveness that consumers can award to wines. Winery size is expected to be inversely related to price (Rodríguez & Castillo, 2009;Kwong et al, 2011;or Delmas & Grant, 2014). Size classification was in accordance with the European Commission (EC) recommendation 6 .…”
Section: Vinos De La Tierra De Castilla Campo De Borja Lamentioning
confidence: 99%
“…This explains the widespread use of hedonic price models to determine the relative importance of the intrinsic characteristics of wine 1 . Some studies are focused on traditional markets, such as France (Landon & Smith, 1997;Lecocq & Visser, 2006;Ali & Nauges, 2007;Cardebat & Figuet, 2009;Carew & Florkowski, 2010), Italy (Brentari et al, 2011 and2015;Caracciolo et al, 2013;Roma et al, 2013;Levaggi & Brentari, 2014;Cacchiarelli et al, 2014) or Germany (Schamel, 2003), as well as new producers, such as Australia (Oczkowski, 1994(Oczkowski, , 2015Steiner, 2004;Davis & Ahmadi-Esfahani, 2005), New Zealand (Bicknell et al, 2005;Bicknell & MacDonald, 2012), US (Yang et al, 2012;Cuellar & Claps, 2013;Delmas & Grant, 2014), Chile (Melo et al, 2005;Troncoso & Aguirre, 2006;Ortuzar & Alfranca, 2010) or Argentina (San Martin et al, 2008;Estrella, 2014).…”
Section: Introductionmentioning
confidence: 99%